100 events that made history : memorable moments that shaped the modern world - "Hibbert, Clare" (New York; DK Publishing, 2016)
This book features fun, informative text and illustrations about one hundred events from history that shaped the modern world
Donated from "Book Planet", Dated 18-4-2025.
Keywords: World history Pictorial works